Neurodegenerative Diseases - Dominguez, Celia; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
The Role of Histone Deacetylases in Neurodegenerative Diseases and Small-Molecule Inhibitors as a Potential Therapeutic Approach.- Phosphodiesterase Inhibition to Target the Synaptic Dysfunction in Alzheimer$1 (Bs Disease.- Glutamate and Neurodegenerative Disease.- Modulation of the Kynurenine Pathway for the Potential Treatment of Neurodegenerative Diseases.- Spinal Muscular Atrophy: Current Therapeutic Strategiess
The Role of Histone Deacetylases in Neurodegenerative Diseases and Small-Molecule Inhibitors as a Potential Therapeutic Approach -- Phosphodiesterase Inhibition to Target the Synaptic Dysfunction in Alzheimer$1 (Bs Disease -- Glutamate and Neurodegenerative Disease -- Modulation of the Kynurenine Pathway for the Potential Treatment of Neurodegenerative Diseases -- Spinal Muscular Atrophy: Current Therapeutic Strategies.s
Keywords: Chemistry; Toxicology; Biochemistry; Neurology; Chemistry; Medicinal Chemistry; Neurology; Pharmacology/Toxicology.